QRIS dan Fragmentasi Sistem Keuangan Global: Tantangan terhadap Hegemoni Keuangan Amerika Serikat - Faiz Mumtaz; Hamemayu Hayuning Bawana; Rizki Ananda Ramadhan (Jurnal Sentris, 2025)
The global financial system has long been dominated by the United States through the power of the US dollar, institutions such as the World Bank and the IMF, and financial infrastructures like SWIFT and Visa. This dependence creates structural vulnerabilities for developing countries. This article analyses how Indonesia utilises the Quick Response Indonesian Standard (QRIS) as a strategic instrument to strengthen financial sovereignty and reduce reliance on a US-centric global financial system. Employing Susan Strange’s (1988) structural power framework, expanded with insights from Helleiner, Norrlof, and Ostrom, this study explores four dimensions of financial structural power: control over credit, capital, and liquidity; the dominance of trade currency; influence over global financial systems; and the ability to shape financial institutions and rules. The findings demonstrate that QRIS represents Indonesia’s effort to expand financial autonomy, enhance domestic economic resilience, and contribute to the fragmentation and emerging multipolarity of the global financial order. This article explains that QRIS is not merely a technical innovation but a strategic instrument within the broader trend of global financial fragmentation.